Solution structure and flexibility of the condensin HEAT-repeat subunit Ycg1 - Manalastas-Cantos, Karen; Kschonsak, Marc; Häring, Christian; Svergun, Dmitri I. (The journal of biological chemistry, 2019)
High-resolution structural analysis of flexible proteins is frequently challenging and requires the synergistic application of different experimental techniques. For these proteins, small-angle X-ray scattering (SAXS) allows for a quantitative assessment and modeling of potentially flexible and heterogeneous structural states. Here, we report SAXS characterization of the condensin HEAT-repeat subunit Ycg1Cnd3 in solution, complementing currently available high-resolution crystallographic models. We show that the free Ycg1 subunit is flexible in solution but becomes considerably more rigid when bound to its kleisin-binding partner protein Brn1Cnd2 The analysis of SAXS and dynamic and static multiangle light scattering data furthermore reveals that Ycg1 tends to oligomerize with increasing concentrations in the absence of Brn1. Based on these data, we present a model of the free Ycg1 protein constructed by normal mode analysis, as well as tentative models of Ycg1 dimers and tetramers. These models enable visualization of the conformational transitions that Ycg1 has to undergo to adopt a closed rigid shape and thereby create a DNA-binding surface in the condensin complex.